Baghdad University /College of Education for Pure Sciences Ibn Al -Haytham /Student Activities Division (Journal of the College of Basic Education, 2022)
In the forefront of the research, on the importance of the training process in raising generations in a proper manner and in various ages, the researchers and thinkers have consistently studied this field in comprehensiveness and depth to reach the best training methods that help those in charge of education in implementing the fullest training curricula and reach an influential training that is reflected On the performance of the players.As for the research problem, the researcher mentioned a weakness in the explosive force of basketball players while following the ball defensively, as it is characterized by weakness in jumping and speed in acquiring the ball defensively, which reflects negatively on the result of the match.The goal was to numbers of self -training exercises (with weight and body weight) in the development of some physical capabilities and the performance of the defensive follow -up skill of basketball.As well as identifying self -training exercises (with weights and body weight) in the development of some physical capabilities and the performance of the defensive follow -up skill of basketball.The researcher assumed that there are statistically significant differences between tribal and dimensional tests and in favor of the remote test The researcher used the experimental curriculum to suit the nature of the problem. The researcher concluded that exercises for self -training (weights and body weight) were effective in developing the explosive force of arms and legs. The researcher recommended the need to use self -training (with weight and body weight) in order to develop other skills, especially the defensive ones.